STRATEGI PEMASARAN TVRI DALAM MENAIKKAN BRAND IMAGE - Christina, Christina (Unitri Press, 2020)
Televisi Republik Indonesia (TVRI) is a state television. Since its establishment on August 24, 1962, TVRI has indeed experienced various phases in its life. Through Law No.32 of 2002 concerning Broadcasting, TVRI was established as a Public Broadcasting Institution (LPP). LPP is a broadcasting institution in the form of a legal entity established by the state, independent, neutral, non-commercial and functions to provide services for the benefit of the community. At present, TVRI has changed its Director since March 2018 namely Helmi Yahya, known as the King of Quiz. With the new Managing Director, TVRI began many enthusiasts who watched with new faces and more interesting programs. This research uses a qualitative research method, and is descriptive in nature which will later explain the marketing strategy of TVRI which has begun to attract the public and an increase in rating and audience share. This study uses interview techniques and data collection from social media and the internet as well as journals, books as primary and secondary data. The marketing strategy undertaken by TVRI includes five rebranding media including channel branding packages, promo on air, news packages, social media, and off air promotions. Of all the rebranding media, the most effective media is social media because aside from being a new media or digital marketing, it can reach all people, both TVRI viewers and private TV viewers